Mechanisms linking economic potential of European cities to housing inequalities of young people - Gerőházi, Éva; Katona, Nóra; Kollár, Sándor György (Frontiers in Sustainable Cities, 2023)
The paper aims to identify and present mechanisms through which the economic potential of European urban areas is converted into social inequalities among the young population in the field of housing. The role of national and local housing systems in this conversion are analysed through the examples of Amsterdam, Tallinn, Chemnitz and Pécs. These four cities represent four major ideal types with different levels of economic power and housing welfare structures.The article, through these case studies, initially delineates the ramifications of increasing housing demand arising from population growth and varied wage structures in cities experiencing economic prosperity. It also delves into the repercussions of population decline and financial constraints in cities with weaker economic foundations. Subsequently, it evaluates the efficacy of local housing policies in addressing housing affordability and spatial segregation, considering the presence of either a unitary or dual public housing sector. The article's conclusion underscores that local housing policies are tightly bound to national housing concepts, legislation, and resources, which constrains their capacity to adapt measures to the changing dynamics of economic development.The primary source of information underpinning this analysis is derived from research conducted in these urban areas as part of the UPLIFT project, funded by the European Commission within the framework of Horizon 2020.